2021
DOI: 10.1039/d1cc00085c
|View full text |Cite
|
Sign up to set email alerts
|

Tilting and twisting in a novel perovzalate, K3NaMn(C2O4)3

Abstract: In the title compound, the oxalate ligand simultaneously bridges both Mn-centred and Na-centred octahedra to produce a unique ‘doubly-interpenetrated’ perovskite-like lattice with an unconventional octahedral tilt system. In turn, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recently it has been shown that divalent oxalate ligands can be incorporated into hybrid perovskite‐like structures. This was first observed in the perovzalates, which adopt A‐site defective A(Li 3 Fe)(C 2 O 4 ) 3 phases that contain a mixture of inorganic A + and, in a 75 : 25 ratio, B + and B 2+ cations [22–25] . These include KLi 3 Fe(C 2 O 4 ) 3 , which has shown potential as a cathode material for K‐ion batteries [24] .…”
Section: Introductionmentioning
confidence: 97%
“…Recently it has been shown that divalent oxalate ligands can be incorporated into hybrid perovskite‐like structures. This was first observed in the perovzalates, which adopt A‐site defective A(Li 3 Fe)(C 2 O 4 ) 3 phases that contain a mixture of inorganic A + and, in a 75 : 25 ratio, B + and B 2+ cations [22–25] . These include KLi 3 Fe(C 2 O 4 ) 3 , which has shown potential as a cathode material for K‐ion batteries [24] .…”
Section: Introductionmentioning
confidence: 97%
“…, polarization beam splitters, circulators, optical isolators, optical microscopes, and so on. Therefore, the search for high-performance birefringent crystals with large birefringence and wide spectral transparency concurrently has always been a scientific hot spot in the fields of optoelectronic functional materials. There are several birefringent materials for commercial applications, such as LiNbO 3 , MgF 2 , YVO 4 , CaCO 3 , α -BBO, etc. Among them, α -BBO has stood out with its excellent comprehensive performance, which not only shows relatively large birefringence (Δ n ≈ 0.142) but also possesses a wide transparent window of 189–3500 nm .…”
Section: Introductionmentioning
confidence: 99%
“…This was first observed in the perovzalates, which adopt A-site defective A(Li3Fe)(C2O4)3 phases that contain a mixture of inorganic A + and, in a 75:25 ratio, B + and B 2+ cations. [22][23][24][25] These include KLi3Fe(C2O4)3, which has shown potential as a cathode material for K-ion batteries. [24] Following from this we have reported the AEr(HCO2)2(C2O4) (A is [(CH3)2NH2] + or [(NH2)3C] + and Ln is a lanthanide) phases, which contain solely A + and B 3+ cations for the first time in a hybrid perovskite structure.…”
Section: Introductionmentioning
confidence: 99%